الرضا الوظيفي لدى معلمي ومعلمات المرحلة الثانوية بمملكة البحرين من وجهة نظرهم - المقابلة، محمد قاسم محمد (جامعة البحرين - مركز النشر العلمي, 2011)
هدفت هذه الدراسة إلى التعرف إلى درجة الرضا الوظيفي التي يحظى بها معلمو ومعلمات المرحلة الثانوية بمملكة البحرين من وجهة نظرهم ، وقد بلغت عينة الدراسة 178 معلما ومعلمة موزعين على (14) مدرسة ثانوية بمملكة البحرين تم اختيارهم بطريقة عشوائية وللإجابة عن أسئلة الدراسة ، قام الباحث بتطوير استبانة خاصة مكونة من (45) فقرة تقيس درجة الرضا الوظيفي عن العمل موزعة على ستة مجالات . \ وقد توصلت الدراسة إلى النتائج الآتية : دلت المتوسطات الحسابية على أن مجالات الرضا الوظيفي لدى معلمي ومعلمات المرحلة الثانوية بمملكة البحرين من وجهة نظرهم مرتبة تنازليا كما يأتي : مجال الوقت وأهميته ، ومجال تقدير الذات ، ومجال مدير المدرسة ، ومجال المسؤولية والعمل ، ومجال الاتجاهات نحو العمل ، ومجال الترقي والأجر. \ أظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية تعزى لأثر الجنس وكانت الفروق لصالح فئة الإناث في المجالات الآتية : مجال مدير المدرسة ، ومجال الترقي والأجر، ومجال الاتجاهات نحو العمل ومجال الوقت وأهميته ، وتبين عدم وجود فروق ذات دلاله إحصائية في مجالي : المسؤولية والعمل ، وتقدير الذات . كما أظهرت النتائج وجود فروق ذات دلالة إحصائية تعزى لأثر سنوات الخبرة في جميع المجالات وفي الأداة ككل، وجاءت الفروق لصالح فئة الخبرة من ( 10-14 سنه)، كما بيئت نتائج الدراسة عدم وجود فروق ذات دلالة إحصائية تعزى لأثر المؤهل العلمي في جميع المجالات وفي الأداة ككل. \ وفي ضوء النتائج التي توصلت إليها الدراسة أوصى الباحث بمجموعة من التوصيات التي يمكن أن تسهم في تحسين الرضا الوظيفي لدى معلمي ومعلمات الثانوية في مملكة البحرين. The study aimed at identifying the degree of job satisfaction of high schools teachers in Bahrain from their point of view. The study sample consisted of (178) teachers in (14) schools for girls and boys in the Kingdom of Bahrain. \ To answer the study questions, the researcher developed a questionnaire. It consisted of (45) items that were divided into (6) domains. \ The results of the study showed that the job satisfaction which were applied by teachers in high schools in Bahrain were as follows: Time domain, self esteem, the headmaster, work and responsibility, attitudes towards work, motivations and the salary. There were statistically significant differences in the status of the gender in all of the domains in favor of female except in two domains: work and responsibility, self average. \ There weren’t statistically significant differences in the status of the experience in all of the domains in favor of the experience between (10-14 years). There weren’t statistically significant differences in the status of educational qualification in all domains. Also, the results showed the teacher’s feelings of dissatisfactions towards motivations, salary, and the load of the school subjects. \ In the light of the results, the researcher recommended some recommendation that would improve teaching aspects of secondary school teachers in the Kingdom of Bahrain that it is necessary to decrease the load of the school subjects in the secondary stage, and necessary to develop a motivation system and increase the teacher’s salary, and adopt different kinds of training programs to focus on the importance of teaching and the role of the teachers in the society’s progress and prosperity. The researcher hopes that these recommendations will be highly considered and benefit education policy planners in Bahrain for the purpose of improving work aspects in teaching.
652716
Keywords: تقدير الذات -- التعليم الثانوي -- الرضا الوظيفي -- معلمو المدارس الثانوية -- البحرين -- أهمية الوقت -- مديرو المدارس الثانوية -- الترقيات -- الأجور -- المسئولية -- الفروق الفردية -- الذكور -- الإناث -- الإدارة المدرسية -- مهنة التدريس -- المكانة الاجتماعية